Graduate Unemployment Hinders Economic Growth in Indonesia: Does Government Spending on Education Matters? - Syarifudin, Achmad; Hamidah , Hamidah; Zainal , Nurazilah; Anwar , Saipul; Shafie, Nur Aima; Liton, Al Mamun (International Journal of Economics and Financial Issues, 2025)
This paper attempts to examine the impact of graduate unemployment on economic growth in Indonesia. Time series data has been included from year 1990 to 2022 and consists of two stages of data analysis. The first stage analysis to identify long-run cointegration between graduate unemployment (GUEM), government spending in education (GEDU), inflation (INF) and foreign direct investment (FDI) towards economic growth by applying the Autoregressive Distributed Lag (ARDL) approach as an estimation method. Second stage analysis determines strength of the relationship by using standard asymptotic Chi-square in Wald test. The findings found that GUEM, GEDU and INF own a significant long run cointegration towards economic growth in Indonesia. This outcome suggests the GUEM lower economic growth due to existence of large mismatch between demand skills by employer and graduate supply by Higher Education which reduce productivity of the whole economy. Meanwhile government spending on education should focus on providing a better infrastructure in higher education to produce quality graduate that matches job requirement in labor market. Overall, the outcomes of this study provide benefits for policymakers to align job demand and production of marketable university graduates from higher education hence boost the economic growth in future.